Television viewing by School-age Children: associations with Physical activity, snack food consumption and unhealthy weight - Nicholson, J.M.; Brown, J.E.; Nicholson, J; Broom, D; Bittman, M (My University, 2011)
Alarm about the increasing prevalence of childhood obesity has focussed attention on individual lifestyle behaviours that may contribute to unhealthy weight. Television viewing is often a focus of the obesity debate. Not only is it sedentary, it also has the potential to influence other lifestyle behaviours either by displacing physical activities or through the consumption of high energy snack foods while watching TV. The research reported here uses data from 2,143 Australian 6–7 year children to examine the lifestyle behaviours associated with excess weight. These children spent 90 min each day watching television, 100 min each day in physical activity, and 39% consumed high levels of snack foods. Nearly one in five (18%) were overweight or obese. After adjustment for family and child characteristics, more time spent watching television was associated with more snacking and less physical activity. However, television viewing was associated with children’s weight status, but snacking and physical activities were not. These findings confirm the existence from a young age, of a cluster of lifestyle behaviours that are associated with unhealthy weight status.
Social Indicators Research
Keywords: Health; Child Development -- Behaviour; Child Development; Childhood and child development; Health and wellbeing; Health; Child Development; Behaviour; Childhood and child development; Health and wellbeing